Determination of Allergen Levels, Isoforms, and Their Hydroxyproline Modifications Among Peanut Genotypes by Mass Spectrometry - Marsh, Justin T.; Palmer, Lee K.; Koppelman, Stef J.; Johnson, Philip E. (Frontiers in Allergy, 2022)
The recently published reference genome of peanuts enables a detailed molecular description of the allergenic proteins of the seed. We used LC-MS/MS to investigate peanuts of different genotypes to assess variability and to better describe naturally occurring allergens and isoforms. Using relative quantification by mass spectrometry, minor variation of some allergenic proteins was observed, but total levels of Ara h 1, 2, 3, and 6 were relatively consistent among 20 genotypes. Previously published RP-HPLC methodology was used for comparison. The abundance of three Ara h 3 isoforms were variable among the genotypes and contributed to a large proportion of total Ara h 3 where present. Previously unpublished hydroxyproline sites were identified in Ara h 1 and 3. Hydroxylation did not vary significantly where sites were present. Peanut allergen composition was largely stable, with only some isoforms displaying differences between genotypes. The resulting differences in allergenicity are of unknown clinical significance but are likely to be minor. The data presented herein allow for the design of targeted MS methodology to allow the quantitation and therefore control of peanut allergens of clinical relevance and observed variability.